PENGARUH INFORMASI KEUANGAN TERHADAP OPINI AUDIT GOING CONCERN - Merry (2014)
his study is performed to examine the effect of Liquidity, Profitability, Leverage and Sales Growth toward going concern audit opinion in manufacturing companies in Indonesian Stock Exchange over period 2010-2012. The population of this research is 131 manufacturing companies listed on the Indonesian Stock Exchange over period 2010-2012. The data is obtained based on corporate finance reporting that at publication. Its gained sample amount of 13 companies from 131 companies those are classified in manufacturing companies in Indonesian Stock Exchange. The analysis technique used here is logistic regression and hypothesis test using t-statistic and coefficients regression with level of significance 5%. The research results that Leverage gives significantly positive effect on going concern audit opinion. The other variables which is Liquidity, Profitability and Sales Growth are not significant to going concern audit opinion. We suggest for public accounting that paying attention other factor that regards to giving going concern audit opinion to audite. On this research, Leverage shows the most influencing variable toward going concern audit opinion one that is pointed out from point acount is even greater instead of t-table and have significance as big as 0,063.